1970
DOI: 10.1002/1097-0142(197011)26:5<965::aid-cncr2820260502>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The histopathology of bronchogenic carcinoma and its relation to growth rate, metastasis, and prognosis

Abstract: During the course of a prospective study in which 6,136 older men were examined by photofluorogram and questionnaire every 6 months, 179 developed proved bronchogenic carcinoma. Histologic sections were obtained in 161 cases and classified by a panel of 3 pathologists using a modified World Health Organization classification. The panel agreed with the diagnoses made by the hospital pathologists in most of those originally classified as squamous cell or adenocarcinoma but classified 30% of the undifferentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

1972
1972
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 9 publications
1
11
0
4
Order By: Relevance
“…A study by Feinstein and associates (75), among 5 pathologists who reviewed 50 lung cancers, revealed a between-observer variability of 2 to 42070 (most marked for poorly differentiated specimens), and a within-observer variability of 2 to 20070. Weiss and associates (76) reported only 400/0 unanimity among 3 pathologists in a review of 161 cases of lung cancer. The poorest agreement, 250/0, occurred with small cell carcinoma.…”
Section: Observer Variabilitymentioning
confidence: 81%
See 1 more Smart Citation
“…A study by Feinstein and associates (75), among 5 pathologists who reviewed 50 lung cancers, revealed a between-observer variability of 2 to 42070 (most marked for poorly differentiated specimens), and a within-observer variability of 2 to 20070. Weiss and associates (76) reported only 400/0 unanimity among 3 pathologists in a review of 161 cases of lung cancer. The poorest agreement, 250/0, occurred with small cell carcinoma.…”
Section: Observer Variabilitymentioning
confidence: 81%
“…It is unfortunate that observer variability was not reported in the studies of the uranium miners, particularly in view of the 25% disagreement reported in earlier studies among pathologists diagnosing small cell carcinoma (75,76). The effect of age on distributions of cell types of lung cancer requires careful attention in studies of environmental exposures inasmuch as small cell carcinoma seems to have a high proportion in young age groups, whereas squamous carcinoma has a high proportion in older age groups (table 2).…”
Section: Clinical Commentarymentioning
confidence: 99%
“…The various ways in which the data have been reported make it almost impossible to refer to the results of other series and make a comparison. However, there have been discrepancies in prognosis, mainly for squamous cell and adenocarcinoma, in series in which tumours have been classified under the same histological headings (Galofre' et al, 1964;Jackman et al;Jones et al, 1967;Weiss et al, 1970). One may say that unanimity in criteria for classification does not exist (Weiss et al, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…However, there have been discrepancies in prognosis, mainly for squamous cell and adenocarcinoma, in series in which tumours have been classified under the same histological headings (Galofre' et al, 1964;Jackman et al;Jones et al, 1967;Weiss et al, 1970). One may say that unanimity in criteria for classification does not exist (Weiss et al, 1970). However, as the survival pattern by histological type varies in relation to the stage of the tumour, discrepancies in survival reported by other authors may reasonably be accepted as a different distribution by stage of the tumours in the various series.…”
Section: Resultsmentioning
confidence: 99%
“…Weiss et al observed that the agreement between pathologists increases if more than one slides is available for review [31]. However, this study was conducted before the introduction of the WHO 1981 classification and it is not clear whether their results are generalizable to the current classification and currently available ancillary techniques.…”
Section: Discussionmentioning
confidence: 81%